Performance and Physiological Responses of Pre-Weaning Peranakan Etawa Goats Fed Milk Replacer with Maggot Flour - Tafsin, Ma'ruf; Sadeli, Achmad; Hanafi, Nevy Diana; Sepriadi, Sigit (Faculty of Agriculture, 2024)
Pre-weaning growth is crucial for achieving high weaning weights, which are expected to positively correlate with the overall performance of does/ewes. Milk replacer, designed to meet the nutritional needs of pre-weaning kids, offers a solution to this challenge. This study aimed to analyze and evaluate the impact of incorporating maggot flour into milk replacer on the performance of pre-weaned Peranakan Etawa (PE) crossbreed goats. The parameters observed included milk replacer intake, nutrient consumption, body weight gain, weaning weight, rectal temperature, respiratory rate, and feed cost per gain. The study involved 10 two-week-old local pre-weaned PE goats, each with an average body weight of 5.33 0.93 kg, divided into two treatment groups with five replicates each. The treatments included a commercial milk replacer (P0) and a milk replacer containing maggot flour (P1). Data were analyzed using an independent t-test at a 5% significance level. The results showed that daily body weight gain in pre-weaned PE goats fed milk replacer containing maggot flour did not differ significantly (P0.05) from those fed the commercial milk replacer. The physiological responses of the pre-weaned goats, including rectal temperature and respiratory rate, were similar between treatments and did not negatively affect their physiological status. The lowest feed cost per gain was observed in the group fed the maggot flour-based milk replacer (P1), indicating its potential economic advantage.